Human Rights and the Protection of Stateless Persons in the Case Law of the European Court of Human Rights (Polish Yearbook of International Law, 2021)
This article analyses the protection of stateless persons under the most recent case law of the European Court of Human Rights (i.e. Hoti v. Croatia and Sudita Keita v. Hungary). The article briefly discusses the phenomenon of statelessness and the basic mechanisms governing it, as well as the general standard for the application of Art. 8 of the European Convention on Human Rights in cases involving foreigners who are stateless. This is followed by a discussion of the aforementioned ECtHR judgments, highlighting their principal findings. Thereafter the impact of UN standards concerning stateless persons on the ECtHR’s reasoning is assessed (based on the UNHCR’s third-party intervention in Hoti), as well as the differences between the approaches taken by the Strasbourg Court and the UN Refugee Agency. Finally, the treatment of foreigners in the Polish legal system is examined, and the importance of the Hoti and Sudita Keita judgments to the potential improvement of the situation of stateless persons in Poland is assessed.